Patterns and Outcomes of Patients with Abdominal Trauma - Ulas Khan, Saman Naz, Talat Shahzad, Hakim Jan, Muhammad Farooq, Nadir Saifullah Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the patterns and outcomes of patients with abdominal trauma. Study Design: Prospective cross sectional study Place and duration of study: Department of Surgery, DHQ Hospital Abbottabad from 1st June 2016 to 30th June 2021. Methodology: One hundred and twenty three abdominal trauma male and female patients having age between 18-45 years. Patients with conservative management and failing to provide history of trauma were excluded from the study. We studied the patterns of abdominal trauma and its outcomes in terms of surgical site infection, anemia, mortality and hospital stay. Results: Majority of the patients were male as compared to females (83.7% vs 16.3%). The most effected age group was 21 to 40 years (56.9%). Road traffic accident was the major cause of injury (59.3%). The most common pattern of injury was blunt force trauma (77.2%). Majority of the patients had < 10 days of hospital stay. Surgical site infection was the most common postoperative complication (36.6%). Mortality rate was 11.4%. Conclusion: Blunt force trauma was the most common pattern of injury. Young patients (21-40 years) were more prone to abdominal injuries. Surgical site infection seems to the most common postoperative complication.